Molecular clusters of the main group elements - Drieß, Matthies; Nöth, Heinrich (Wiley-VCH, 2004)
Molecular Clusters of the Main Group Elements; Contents; Preface; List of Contributors; 1 Theory and Concepts in Main-Group Cluster Chemistry; 2.1 Homonuclear Boron Clusters; 2.2 Boron Clusters in Medical Applications; 2.3 Clusters of the Heavier Group 13 Elements; 2.4 Discrete and Extended Metal Clusters in Alloys With Mercury and Other Group 12 Elements; 2.5 Molecular Cages and Clusters of the Heavier Group 14 Elements (E = Si, Ge, Sn or Pb) of Formula E(n)R(m) (n m); 2.6 Homoatomic Cages and Clusters of the Heavier Group 15 Elements: Neutral Species and Cations.
Includes bibliographical references (pages 421-424) and index
Keywords: Aufsatzsammlung; Clusterverbindungen; Hauptgruppenelementverbindungen